SPECIFIC FEATURES OF TEACHING THE MOTHER TONGUE THROUGH FICTION (International journal of artificial intelligence, 2026)
This article is dedicate to the problem of using literaru texts in teaching language phenomena at the lessons of mother tongue in primary classes. It is practicaly stated peculiar points of teaching lexic-grammatic features of parts of speech in using literary texts.